Probiotics - Current Knowledge and Future Prospects 2018
DOI: 10.5772/intechopen.72804
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Probiotics and Novel Probiotic-Based Approaches for Infectious Diseases

Abstract: Probiotics are live microorganisms, which confer health benefits on host when administered in adequate amounts. Probiotics exert their beneficial effects by maintenance flora healthy, enhancement of mucosal barrier integrity and modulation of immune responses. Antimicrobial substances including bacteriocins, hydrogen peroxide, organic acids, and short-chain fatty acids (SCFAs) produced by probiotics allow them to inhibit mucosal and epithelial adherence of pathogens and compete for limiting resources, thus sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Other antimicrobial molecules released by probiotic bacteria are hydrogen peroxide (H 2 O 2 ) and extracellular high molecular weight sugar polymers known as exopolysaccharides (EPS). Hydrogen peroxide produced by lactobacilli may oxidize different compounds (proteins, nucleic acids, and lipids) of pathogenic microorganisms, thus leading to significant impairments in structure and possibly to the loss of cell viability [ 52 , 53 ]. On the other hand, although the mechanism of action is not yet clear, it has been shown that EPS from lactobacilli and bifidobacteria plays an important role in protecting pathogenic bacteria such as enterotoxigenic E. coli and Citrobacter rodentium [ 54 , 55 ].…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Other antimicrobial molecules released by probiotic bacteria are hydrogen peroxide (H 2 O 2 ) and extracellular high molecular weight sugar polymers known as exopolysaccharides (EPS). Hydrogen peroxide produced by lactobacilli may oxidize different compounds (proteins, nucleic acids, and lipids) of pathogenic microorganisms, thus leading to significant impairments in structure and possibly to the loss of cell viability [ 52 , 53 ]. On the other hand, although the mechanism of action is not yet clear, it has been shown that EPS from lactobacilli and bifidobacteria plays an important role in protecting pathogenic bacteria such as enterotoxigenic E. coli and Citrobacter rodentium [ 54 , 55 ].…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…36 Moreover, bacteriocins produced by L. plantarum effectively inhibit the growth of Staphylococcus aureus, Listeria monocytogenes and other bacteria. 37 These findings demonstrate the potential of L. plantarum as a probiotic in aquaculture, offering a viable alternative to antibiotics for disease prevention and control.…”
Section: Introductionmentioning
confidence: 78%
“…"They also act as a barrier to prevent the adherence of pathogenic bacteria, by interfering with colonization and proliferation of pathogens, thereby preventing the manifestation of infections" [21]. "Lactobacilli species also produces antimicrobial peptides (bacteriocins), organic acids (acetic acid and lactic acid), and other metabolites (hydrogen peroxide), which are reported to inhibit the growth of pathogenic bacteria" [22]. "Probiotic strains of Lactobacillus plantarum also participate in the absorption of water and sodium in the colon and decrease diarrhoea symptoms.…”
Section: Introductionmentioning
confidence: 99%